(untitled) (Ukrainian Journal of Ophthalmology, 2026)
Objective: This study aimed to compare the indications, timing, and clinical outcomes of phakic implantable collamer lens (ICL) exchange or explantation between eyes with keratoconus and eyes without keratoconus or other corneal ectasia (non-ectatic eyes), and to evaluate factors associated with the need for secondary ICL intervention, at a tertiary eye hospital in Iraq. Methods: This retrospective record review included ICL (V4b) procedures performed between January 2022 and January 2024. Among 200 implanted eyes, 25 eyes (12.5%) underwent secondary surgery and were included for group comparison: keratoconus group (n=10) and non-ectatic group (n=15). Clinical data included visual acuity, refraction, intraocular pressure, endothelial cell density, corneal parameters, and vault. Comparative analyses were performed between groups, with p<0.05 considered statistically significant. Results: In the keratoconus group, ICL exchange occurred in 5/10 (50.0%) and explantation in 5/10 (50.0%); in the non-ectatic group, exchange occurred in 8/15 (53.3%) and explantation in 7/15 (46.7%). The primary indications for exchange/explantation differed between groups. In keratoconus eyes, indications were vault-related issues (7/10; 70.0%), residual refractive concerns (2/10; 20.0%), and patient dissatisfaction (1/10; 10.0%). In non-ectatic eyes, indications were vault-related issues (9/15; 60.0%), cataract (2/15; 13.3%), elevated intraocular pressure (2/15; 13.3%), refractive concerns (1/15; 6.7%), and patient dissatisfaction (1/15; 6.7%). Conclusion: ICL exchange or explantation occurred in 12.5% of implanted eyes in this cohort. Vault-related indications were the most common reason for secondary intervention in both groups, while cataract and elevated intraocular pressure were observed only in the non-ectatic group. These findings support careful sizing/vault assessment and structured follow-up in eyes undergoing ICL implantation.